Prevalence of Obesity in Women with Polycystic Ovarian Syndrome: A Retrospective Report (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2020)
Background: Polycystic Ovarian Syndrome (PCOS) is one of the ten most common gynaecological problems and the leading cause of female infertility. PCOS not only affects the physical health, but also the mental health of women. Prevalence of higher levels of psychological distress in women with PCOS has been well documented. Obesity which also leads to psychological stress and issues too has been documented as a cause of PCOS. Objective: Despite the increasing incidence of the syndrome, limited research has been done to study the obesity in women who were diagnosed to have PCOS. Methodology: The data of 73 women who approached the institution for diagnosis and management of PCOS were included in the study. Demographic data like age, height and weight of the women at the time of diagnosis of PCOS were collected and subjected to analysis. Result: The results showed that 42% women had normal BMI and 14% were underweight. Overweight and obese women constituted 22% each. Conclusion: The result of the study suggests that obesity and overweight may not necessarily be the cause of PCOS.
Keywords: Polycystic Ovarian Syndrome; BMI; Obesity; Prevalence.